PENGARUH ASBUTON SEMI EKSTRAKSI PADA CAMPURAN STONE MASTIC ASPHALT - Furqon Affandi (Jurnal Jalan-Jembatan, 2010)
The most pavement type in Indonesia is flexible pavement, of which rutting as one of the pavement defect is caused by heavy load and high temperature. Rutting can cause the decrease of road service and followed by crack which leading to worse damage of pavement. The purpose of the study is to find out the performance of Stone Mastic Asphalt using asphalt cement pen 60 mixed with semi extraction of asbuton and the method of the research is laboratory experiments. The results showed that the addition of semi extraction asbuton significantly increases the resistance of the SMA mixtures to rutting, increasing modulus of asphalt mixtures and improve drain down and flushing. However the resistance of mixture to particle loose decreases even though it is still in the limit requirement and it tends to become less brittle. As the addition of semi extraction asbuton increases some Stone Mastic Asphalt performance, and decreases the others, so that the determination of semi extraction asbuton proportion has to be minimum but still meet the requirement of asphalt mixture, by carrying further research about fatigue resistance of Stone Mastic Asphalt Keywords : Stone Mastic Asphalt, rutting, asphalt cement pen 60, stiffness modulus, semi extraction Asbuton.